Colonial Version of The Chinese Chronicles from Sam Po Kong Temple As a Historical Evidence - Widyo Nugrahanto; Etty Saringendyanti; Eko Wahyu Koeshandoyo; Tanti Restiasih Skober; Ayu Septiani (Badan Riset dan Inovasi Nasional (BRIN), 2024)
This article discusses the result of research on a manuscript called Chinese Chronicles on Sam Po Kong Temple found in a manuscript from Cirebon. This research used a historical method consisting of 4 stages: heuristics, criticism interpretation, and historiography using analytic descriptive method. This research aims to prove that the chronicles are as secondary historical evidence, not a primary one. These Chinese chronicles are a copy of the manuscript. It is estimated that the copy was made in the Dutch colonial era after 1928. The Chronicles tell the life of the Moslem Chinese in Nusantara, especially Java Island, after Cheng Ho’s voyage to Nusantara when it was still under Majapahit kingdom sovereignty.